2010
DOI: 10.1021/tx1000893
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation Inhibition, DNA Damage, and Cell-Cycle Arrest of Human Astrocytoma Cells after Acrylamide Exposure

Abstract: Acrylamide (ACR) has been recognized as a neurological and reproductive toxin in humans and laboratory animals. This study aimed to determine the effects of ACR-induced DNA damage on cell cycle regulation in human astrocytoma cell lines. Treatment of U-1240 MG cells with 2 mM ACR for 48 h resulted in a significant inhibition of cell proliferation as evaluated by Ki-67 protein expression and MTT assay. The analysis of DNA damage with the comet assay showed that treatment of the cells with 0.5, 1, and 2 mM ACR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
10
23
0
Order By: Relevance
“…Okuno et al (2006) reported that the ERK pathway causes phosphorylation of p53 at Ser15 and the cytotoxicity of ACR in SH-SY5Y cells without RA-induced differentiation. Our previous studies showed that ACR induced cytotoxicity in U-1240 MG cells through the phosphorylation of p53 at Ser15 during ATM/ATR signaling (Chen et al, 2010). The current study further demonstrated that the phosphorylation of ERK and JNK were decreased by ACR exposure in U-1240 MG cells without BA-induced differentiation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Okuno et al (2006) reported that the ERK pathway causes phosphorylation of p53 at Ser15 and the cytotoxicity of ACR in SH-SY5Y cells without RA-induced differentiation. Our previous studies showed that ACR induced cytotoxicity in U-1240 MG cells through the phosphorylation of p53 at Ser15 during ATM/ATR signaling (Chen et al, 2010). The current study further demonstrated that the phosphorylation of ERK and JNK were decreased by ACR exposure in U-1240 MG cells without BA-induced differentiation.…”
Section: Discussionsupporting
confidence: 78%
“…The toxic effects of ACR on neurons have been investigated intensively, including the reduction of cell viability, the induction of apoptosis and p53 phosphorylation (Okuno et al, 2006;Sumizawa and Igisu, 2007), the formation of perikaryal inclusion bodies (Hartley et al, 1997), and the neurodegeneration of signal transduction (Yuzo et al, 2001). ACR-induced DNA breaks will increase p21 expression and G0/G1 cell-cycle arrest by inhibiting cyclin D1/Cdk4/6 kinase activity, which in turn causes cellular mitochondria collapse and apoptosis (Chen et al, 2010(Chen et al, , 2013. Our study further suggested that ACR impairs the differentiation efficiency of human neurons and glia cells and that the interactions of neurons and glia cells in the neuronal system may be affected by ACR-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Nonetheless, considering the previously obtained results in cellular proliferation, an increase in the number of cells in the G1 phase of the cell cycle would make sense. In fact, cell cycle arrests cause decrease in cellular proliferation (Chen et al, 2010).…”
Section: Effect Of Extract 2 On Nci-h460 Cell Cycle Profilementioning
confidence: 99%